Behavioral Response of Non-Resident Parents to Child Support Obligations: Evidence From SOEP - Marianna Schaubert (ZBW – Leibniz Information Centre for Economics, 2018)
The present paper investigates how parents responsible for child maintenance payments have responded to changes in the amount of obligations. The potential endogeneity of child support obligations is addressed by using SOEP panel data from 1985-2013 and applying individual FE-IV models. Results for parents younger than 50 years old show that a euro 10 increase in monthly child support obligations decreases the likelihood of having an additional child by about 0.39 percentage points (about 3% at the sample mean). Furthermore, an increase in financial obligations does not have an impact on the likelihood of cohabiting with a new partner or on hours spent with children entitled to child support. There is only weak evidence of a positive (re)marriage incentive. There seems to be no adjustment in the parent's labor supply. To my knowledge, the present investigation is the first causal analysis of the behavioral response of non-resident parents to child support obligations in Germany.
Keywords: J12; J13; J16; K36; 330; Child support; Child support policy; Non-resident parents; Labor Supply; Childcare